Mn0.8Zn0.2Fe2O4 nanoparticulates spinel ferrites: An approach to enhance the antenna field strength for improved magnitude versus offset (MVO) - Niaz Akhtar, M. (Elsevier B.V., 2014)
Electromagnetic signals in deep reservoir are very weak so that it is difficult to predict about the presence of hydrocarbon in seabed logging (SBL) environment. In the present work, Mn0.8Zn0.2Fe2O4 nanoferrites were prepared by a sol-gel technique at different sintering temperatures of 450°C, 650°C and 850°C to increase the strength of electromagnetic (EM) antenna. XRD, FESEM, Raman spectroscopy and HRTEM were used to analyze the phase, surface morphology and size of the nanoferrites. Magnetic properties of the nanoferrites were also measured using an impedance network analyzer. However, nanoferrites sintered at 850°C with initial permeability of 200 and Q factor of 50 were used as magnetic feeders with the EM antenna. Lab scale experiments were performed to investigate the effect of magnetic field strength in scale tank. SPSS and MATLAB softwares were also used to confirm the oil presence in scale tank. It was observed that the magnitude of the EM waves for the antenna was increased up to 233. Finally, the correlation values also show 208 increase in the magnetic field strength with the presence of the oil. Therefore, antenna with Mn0.8Zn0.2Fe2O4 nanoferrites based magnetic feeders can be used for deep water and deep target hydrocarbon exploration. © 2014 Chinese Materials Research Society.